Hubungan Self Compassion Dengan Emotion-Focused Coping Pada Mahasiswa Yang Sedang Mengerjakan Skripsi Di Kampus X Padang - Sianipar, Nuryati; Pratama, Mario (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
The purpose of this study is to investigate the relationship between self compassion and emotion-focused coping among students currently working on their thesis at Campus X, Padang. This research employs a quantitative correlational design. The sample consists of 225 students who are engaged in thesis work at Campus X, Padang, selected using purposive sampling. The research utilizes a Likert scale instrument constructed based on aspects from Lazarus and Folkman for the emotion-focused coping variable, and Kristin D. Neff for the self compassion variable. Hypothesis testing employs the product moment correlation method with the assistance of SPSS 20 for Windows. The research findings yielded a correlation coefficient of 0.105 with a significance level of 0.115. Thus, it can be concluded that there is no relationship between self compassion and emotion-focused coping among students who are working on their thesis at Campus X, Padang. The implications of this study suggest that future researchers should consider modifications or the adoption of new theories, as well as the exploration of different independent variables, changes in research subjects, or the use of different research methods to delve deeper into this phenomenon.